Regenerar, civilizar, modernizar e nacionalizar : a educação física e a infância em revista nas décadas de 1930 e 1940 - Berto, Rosianny Campos (2008)
The work aims at understanding the way how the representations on children education in or outside the school were produced and transmitted during 1930 and 1940, investigating how the knowledge was approached by different groups of intellectuals that projected Physical Education in that period. It uses as sources/objects the Revista de Educação Física (do Exército) and the magazine called Educação Physica, periodicals circulating simultaneously during the years 1932 and 1945 in Brazil, and constituted a documental study corpus. The first one is a strategic device of the soldiers of the Escola deEducação Física do Exército and the second, produced as tactics that represent the ideals of a group of Physical Education teachers linked to the Christian Association of Boys. It analyses the way the prescription produced by the intellectual groups that supported the periodicals, for instance, necessary knowledge to the children education circulated in that period. It uses as theoretical referential the cultural history and the propositions related to the attention to objects in its materiality. This way, the study stands out the discursive and non-discursive devices that modeled the ways to give meaning to Physical Education when highlighting children education. It examines the representations fights(CHARTIER, 1988) by actors who, in the production of the printed material like power places (CERTEAU, 2004), made knowledge to circulate and gave to reading and seeing exemplary forms of projecting Physical Education as a school subject and as an extra-curricular practice. The thematic transmitted by the magazines make possible the visualization of approximations and separations among them, so that similarities were indicated in relation to prescriptions for Physical Education. When centered on children education, both circulars had as motto the senses education. It is also possible to note that both periodicals present the game as the main content prescribed for children, it would assist best the children peculiarities, emphasizing that, in the school ambit, such prescriptions used the French method as parameter, made official in Brazilian schools. Thus, when looking at the ones who produced the periodicals and the ones who wrote for them, it is possible to note the existence of certain circulation of that actors by space in constitution, it is possible to realize representations shared and the cordialities relations, creating sociability nets (SIRINELLI, 1996) at the same time when it is possible to highlight that, in this movement, the competition by the dominion of such place of authorized speech is present. The prescriptions transmitted in the magazines enabled the understanding that the Physical Education school ideal was marked by places of power where actors from different groups of the magazine used to speak. However, the knowledge indicates common goals focusing on the formation of “children souls” and the preparation for the future. Education project that implicated the change of behaviors and acquisition of healthy and hygienic habits thatcould reflect an ideal of new man and of regenerated race, accordant with the modern proposals in evidence in the first decades of the twentieth century in the country.